Synthesis and Microbial Activity of Transition Metal Complexes of 3-Phenyl Rhodanine - Kshirsagar, Versha; Gandhi, Sandhya; Dave Gautam, Mangla (Asian Journal of Chemistry, 2010)
Compounds containing thiazole moiety are known to possess various biological activities. Rhodanine and substituted rhodanine, which contain toxiphoric dithiocarbamate chromophore (NCSS) are reported to be excellent fungicides and bacteriocides. A large number of 3- and 5-substituted rhodanine derivatives were synthesized and investigated for antibacterial and antifungal activities. It is known that some drugs have increased activity when administered as metal complexes. In cancer treatment it has been shown that the active species is the metal chelate of the drug. Antimicrobial activity of 3-phenyl rhodanine and its metal complexes in dimethyl formamide was studied by serial tube dilution technique. The solution was added to N-Broth to get 200, 100, 50, 25, 12.5 6.25, 3.125 and 1.56 μg/mL concentration. 3-Phenyl rhodanine is found to be active against S. areaus and P. aeruginosa. Minimum inhibitory concentration value is found to be 200 μg, which is important from the clinical viewpoint. The compound is less active against B. subtilis and E. coli and MIC values are found to be above 200 μg. Metal complexes of 3-phenyl rhodanine are found to be less active than parent compound and MIC was above 200 μg except Cu.